Sandy soils in the forests of northern Michigan (USA) as methane sinks: Impacts of tree species composition and winter snowpacks - Chase S. Kasmerchak; David E. Rothstein; J. Randal Schaetzl (Forest Ecology and Management, 2025)

Phenology Across Scales: An Intercontinental Analysis of Leaf‐Out Dates in Temperate Deciduous Tree Communities - Nicolas Delpierre; Suzon Garnier; Hugo Treuil‐Dussouet; Koen Hufkens; Jianhong Lin; Colin Beier; Michael Bell; Daniel Berveiller; Matthias Cuntz; Giulio Curioni; Kyla Dahlin; Sander O. Denham; et al. (Global Ecology and Biogeography, 2024)
Aim To quantify the intra‐community variability of leaf‐out (ICVLo) among dominant trees in temperate deciduous forests, assess its links with specific and phylogenetic diversity, identify its environmental drivers and deduce its ecological consequences with regard to radiation received and exposure to late frost. Location Eastern North America (ENA) and Europe (EUR). Time Period 2009–2022. Major Taxa Studied Temperate deciduous forest trees. Methods We developed an approach to quantify ICVLo through the analysis of RGB images taken from phenological cameras. We related ICVLo to species richness, phylogenetic diversity and environmental conditions. We quantified the intra‐community variability of the amount of radiation received and of exposure to late frost. Results Leaf‐out occurred over a longer time interval in ENA than in EUR. The sensitivity of leaf‐out to temperature was identical in both regions (−3.4 days per °C). The distributions of ICVLo were similar in EUR and ENA forests, despite the latter being more species‐rich and phylogenetically diverse. In both regions, cooler conditions and an earlier occurrence of leaf‐out resulted in higher ICVLo. ICVLo resulted in ca. 8% difference of radiation received from leaf‐out to September among individual trees. Forest communities in ENA had shorter safety margins as regards the exposure to late frosts, and were actually more frequently exposed to late frosts. Main Conclusions We conducted the first intercontinental analysis of the variability of leaf‐out at the scale of tree communities. North American and European forests showed similar ICVLo, in spite of their differences in terms of species richness and phylogenetic diversity, highlighting the relevance of environmental controls on ICVLo. We quantified two ecological implications of ICVLo (difference in terms of radiation received and exposure to late frost), which should be explored in the context of ongoing climate change, which affects trees differently according to their phenological niche.

Evaluating essential oils as biocidal anti-drift adjuvants for safe and sustainable agricultural spray enhancement - Joseph Heng; Samuel Bechard; David Lach; Jonathan Rothstein; Minghe Wang; Sebastian Ubal; David Julian McClements; Carlos M. Corvalan; Jiakai Lu (Journal of Aerosol Science, 2024)

Management of tree density to sustain Kirtland’s warbler breeding habitat and timber production from jack pine plantations - Megan Machusko; David E. Rothstein; Amy D. Bleisch (Forest Ecology and Management, 2024)

Changes in ecosystem nutrient pools through stand development following whole-tree harvesting of jack pine (Pinus banksiana) on sandy, nutrient poor soils in northern Lower Michigan - David E. Rothstein; Daphna Gadoth-Goodman (Forest Ecology and Management, 2023)

The Toxicology Investigators Consortium Case Registry—the 2021 Annual Report - Jennifer S. Love; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; HoanVu Nguyen; Sharan L. Campleman; Shao Li; Paul M. Wax; Jeffery Brent; Kim Aldy; Michael Abesamis; et al. (Journal of Medical Toxicology, 2022)

Alternative Silvicultural Approaches to Managing Jack Pine Plantations for Endangered Species Habitat and Forest Products - Daphna Gadoth-Goodman; David E Rothstein (Forest Science, 2020)
Since the early 1980s, ca 1,550 hectares (3,800 ac) of high-density jack pine (Pinus banksiana) plantations have been established annually in northern Lower Michigan to serve as habitat for the federally endangered Kirtland’s warbler (KW; Setophaga kirtlandii). Because these plantations do not appear capable of producing merchantable sawlogs by their planned 50-year harvest age, we investigated the potential to implement reduced rotation lengths in these stands to produce biomass and/or pulpwood. We used space-for-time substitution to assess biomass and volume accrual over time, using our own locally derived allometric biomass equations. The predicted optimal rotation age for biomass was 20 years, and the predicted optimal rotation age for pulpwood volume was 28 years. We compared the total land area required for management under these rotation scenarios to continue establishing 1,550 hectares (3,800 ac) of KW habitat annually. Management on the current 50-year cycle requires ca 77,500 hectares (191,500 ac). Management for pulpwood would reduce this to ca 43,400 hectares (107,250 ac), and management for biomass would require ca 31,000 hectares (76,600 ac). Our results suggest that rotation lengths in these plantations could be substantially reduced, allowing for reductions in the total land area dedicated to warbler habitat, allowing for diversification of management at the landscape scale.

Patterns of DON and DOC Leaching Losses Across a Natural N Availability Gradient in Temperate Hardwood Forests - Emily E. Scott; David E. Rothstein (Ecosystems, 2017)

Jack pine foliar δ15N indicates shifts in plant nitrogen acquisition after severe wildfire and through forest stand development - Stephen D. LeDuc; David E. Rothstein; Zhanna Yermakov; Susan E. Spaulding (Plant and Soil, 2013)

Ectomycorrhizal fungal succession coincides with shifts in organic nitrogen availability and canopy closure in post-wildfire jack pine forests - Stephen D. LeDuc; Erik A. Lilleskov; Thomas R. Horton; David E. Rothstein (Oecologia, 2013)

Soil microbial biomass as affected by groundcover management in a Fraser fir (Abies fraseri [Pursh] Poir) plantation after 1 year - Paligwende Nikièma; Pascal Nzokou; David E. Rothstein; Mathieu Ngouajio (Biology and Fertility of Soils, 2012)

Effects of groundcover management on soil properties, tree physiology, foliar chemistry and growth in a newly established Fraser fir (Abies fraseri [Pursh] Poir) plantation in Michigan, United States of America - Paligwende Nikiema; Pascal Nzokou; David Rothstein (New Forests, 2012)

Amino acid uptake by temperate tree species characteristic of low- and high-fertility habitats - Emily E. Scott; David E. Rothstein (Oecologia, 2011)

Quantifying Terrestrial Ecosystem Carbon Dynamics in the Jinsha Watershed, Upper Yangtze, China from 1975 to 2000 - Shuqing Zhao; Shuguang Liu; Runsheng Yin; Zhengpeng Li; Yulin Deng; Kun Tan; Xiangzheng Deng; David Rothstein; Jiaguo Qi (Environmental Management, 2010)

Plant‐available organic and mineral nitrogen shift in dominance with forest stand age - Stephen D. LeDuc; David E. Rothstein (Ecology, 2010)
Studies of soil nitrogen (N) availability over stand development have almost exclusively focused on mineral N, yet we increasingly recognize that plants can take up organic N in the form of free amino acids at biologically important rates. We investigated amino‐acid and mineral N availability along a 10‐site chronosequence of jack pine stands, varying in age from 4 to 60 yr following wildfire. We measured free amino‐acid N and mineral N in soil extracts; native proteolytic rates; net N mineralization rates; and microbial amino‐acid consumption via a 15 N leucine tracer assay in 6 of the 10 sites (4, 10, 18, 22, 46, and 55‐yr‐old). Amino‐acid N was consistently low in the youngest sites (4–10 yr), increased rapidly in mid‐aged sites (15–22 yr), and was highest in stand age 46. In contrast, mineral N exhibited a parabolic shape ( R 2 = 0.499; P P = 0.632). Percentage 15 N tracer recovery was lowest in the extractable organic N pool for the 4, 10, and 18‐yr‐old sites, though only site age 10 was significantly different from the older sites. Percentage of recovery in the organic N pool was significantly positively related ( R 2 = 0.798; P

Changes in soil carbon and nitrogen cycling along a 72-year wildfire chronosequence in Michigan jack pine forests - Zhanna Yermakov; David E. Rothstein (Oecologia, 2006)

Modeling Ocean Ecosystems: The PARADIGM Program - Lewis Rothstein; John Cullen; Mark Abbott; Eric Chassignet; Ken Denman; Scott Doney; Hugh Ducklow; Katja Fennel; Mick Follows; Dale Haidvogel; Eileen Hofmann; David Karl; et al. (Oceanography, 2006)

Nitrogen Management in a Fraser Fir ( Abies fraseri [Pursh] Poir.) Christmas Tree Plantation: Effects of Fertilization on Tree Performance and Nitrogen Leaching - David E. Rothstein (Forest Science, 2005)
There is increasing concern over the effects of nitrogen (N) pollution resulting from fertilizer inputs to food and fiber production systems. Christmas tree production is one segment of the forestry sector that uses substantial fertilizer inputs. However, we know very little about the environmental costs and production benefits of N fertilization in Christmas tree plantations. I studied the costs and benefits of 2 years of N applications (as ammonium sulfate) at 0, 47, 95, and 140 kg N ha−1 year−1 to 4-year-old Fraser fir (Abies fraseri) Christmas trees. These rates correspond to 0, 50, 100, and 150% of the amount recommended for 4-year-old trees, and 33, 67, and 100% of recommendations for 5-year-old trees. There were no significant effects of fertilization rate on tree growth or morphology. In contrast, foliar N concentrations increased with increasing rates of N application, and there was a trend toward improved foliage health (indicated by chlorophyll fluorescence) at the lowest application rate. Mineral N (NH+4 + NO−3) concentrations in water leaching below the rooting zone increased markedly with increasing N application rates. Lysimeter NO−3 concentrations in the highest application treatment were consistently 20–30 times greater than the safe drinking water standard of 10 mg NO−3-N/l. Together, these results suggest that conventional guidelines for fertilization of Michigan Fraser fir plantations greatly exceed the capacity of trees and surface soils to store N, provide no benefit to tree growth, and create the potential for significant N pollution of ground and surface waters. Furthermore, these results indicate that applying N at a lower rate of 47 kg N ha−1 year−1 substantially reduced NO−3 leaching with no decline in growth rates or tree quality. FOR. SCI. 51(2):175–184.

An Exotic Tree Alters Decomposition and Nutrient Cycling in A Hawaiian Montane Forest - David E. Rothstein; Peter M. Vitousek; Breana L. Simmons (Ecosystems, 2004)

Heavy metal and selenium levels in young cattle egrets from nesting colonies in the northeastern United States, Puerto Rico, and Egypt - Joanna Burger; Katharine Parsons; Thomas Benson; Tara Shukla; David Rothstein; Michael Gochfeld (Archives of Environmental Contamination and Toxicology, 1992)